2005
DOI: 10.1051/lait:2005017
|View full text |Cite
|
Sign up to set email alerts
|

Lactose crystallisation and early Maillard reaction in skim milk powder and whey protein concentrates

Abstract: -Lactose crystallisation and Maillard reaction are two major modifications occurring in milk and whey powders during processing and storage. In this work, the aim was first to monitor the solid-state early Maillard reaction (EMR) in whey protein concentrates (WPC) heated at 60 °C and various water activities, and then, to characterise the physical changes that occur as a consequence of heat treatment in skim milk powder (SMP) and WPCs. After a w adjustment, SMP and WPC were heated at 60 °C in hermetic conditio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
24
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(33 citation statements)
references
References 16 publications
(23 reference statements)
4
24
0
Order By: Relevance
“…Although, at 50 and 60 C and at the same RH, faster crystallization could be expected, there were no significant differences between the rate constant values of samples equilibrated at a w 0.33 and 0.43 at 50 and 60 C. Apparently, in this study crystallization of lactose had no effect on the reactivity of lysine. Similar results were reported by other authors (Morgan, Appolonia Nouzille, Baechler, Vuataz, & Raemy, 2005;Vuataz, 1988) who suggested that, despite the fact that an increase of a w could accelerate NEB, crystallization immobilizes lactose and thus less dissolved lactose is available for reaction with proteins. It should be noted that a w could also rise during storage, as water is a product of Maillard reaction.…”
Section: Effect Of a W On Rate Constantssupporting
confidence: 90%
“…Although, at 50 and 60 C and at the same RH, faster crystallization could be expected, there were no significant differences between the rate constant values of samples equilibrated at a w 0.33 and 0.43 at 50 and 60 C. Apparently, in this study crystallization of lactose had no effect on the reactivity of lysine. Similar results were reported by other authors (Morgan, Appolonia Nouzille, Baechler, Vuataz, & Raemy, 2005;Vuataz, 1988) who suggested that, despite the fact that an increase of a w could accelerate NEB, crystallization immobilizes lactose and thus less dissolved lactose is available for reaction with proteins. It should be noted that a w could also rise during storage, as water is a product of Maillard reaction.…”
Section: Effect Of a W On Rate Constantssupporting
confidence: 90%
“…Lactose crystallization may depend on the lactose protein ratio in milk powder. Crystallization is easily induced in skim milk powder (SMP), whereas it is delayed or even inhibited in whole milk powder (WMP) (Morgan et al 2005). Thomas et al reported that interactions between β-lactoglobulin and lactose resulted in stabilization of β-lg-lactose (90:10) powder against lactose crystallization and the lactose crystallization was delayed (Thomas et al 2005).…”
Section: Lactose Crystallizationmentioning
confidence: 99%
“…The nonenzymatic reaction can occur progressively during storage. The nature and extent of the Maillard reaction depend on numerous factors, including water activity, pH, temperature, and physicochemical state of the component (Morgan et al 2005). In milk products, the Maillard reaction begins by lactose condensation on some amino acid residues (lactosylation) and involves a wide range of subsequent reactions (Thomas et al 2004).…”
Section: Maillard Reactionmentioning
confidence: 99%
“…Even for the dry-state lactosylation, the water activity is a major determinant for the reaction, the rate of reaction being maximal at intermediate water activities (0.4e0.8) due to the dual effect of water acting as a reaction product (mass-law retardation) and increasing the mobility of the reactants ( van Boekel, 2001;Labuza & Baisier, 1992;Morgan, Nouzille, Baechler, Vuataz, & Raemy, 2005;Saltmarch, Vagnini-Ferrari, & Labuza, 1981).…”
Section: Introductionmentioning
confidence: 99%
“…The authors therefore speculated that the attachment of one lactose molecule to b-LG may make the protein less prone to react with the next lactose molecule. Despite the very small structural changes induced by the dry-state lactosylation (Medranoa et al, 2009), this might also be the case for dry-state lactosylation of b-LG, since the lactosylation reaction between b-LG and lactose in whey protein concentrate in the dry-state (a w 0.2e0.4) proceeded non-linearly with time at both 35 and 60 C, as measured by the percentage of blocked lysine residues (Morgan et al, 2005). Therefore, there is a need to study the kinetics of the initial steps in the lactosylation process in more detail.…”
Section: Introductionmentioning
confidence: 99%